Politics Cast Shades on Private Lives in David Rabe and David Hare’s Works - Attia, Sarah (Journal of Ecohumanism, 2024)
This study examines some works of playwrights David Rabe and David Hare, focusing on how politics permeate and cast shades on private lives in their plays. Rabe and Hare are known for their ability to provoke and explore burning themes within their societies. Through their unique theatrical styles, they effectively reflect their visions of significant social and political aspects. It depends on the analytical and comparative approaches to analyze thoroughly the ways in which Rabe and Hare incorporate political elements into their works, ultimately shedding light on the intricate relationship between politics and private lives and how theater can serve as a potent medium for engaging in social and political discourse within the context of their works, and the insights that can be gained from comparing their plays regarding how politics influence personal experiences, values, and choices. The study raises several substantive questions concerning Rabe and Hare’s plays: How do they incorporate political elements into their plays? What are the effects of politics on characters' private lives in Rabe's "Sticks and Bones" and "The Basic Training of Pavlo Hummel"? How do they depict the psychological impact of war and political ideologies on individuals and their families? In what ways do Hare's plays, such as "Plenty" explore the disillusionment, compromises, and personal sacrifices stemming from specific political contexts? How do they navigate the complex interplay between personal convictions and the pressures of ideology in their plays?